2018
DOI: 10.5005/jp-journals-10055-0048
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the Management of Snakebites

Abstract: India is estimated to have the highest snakebite mortality in the world. World Health Organization (WHO) places the number of bites to be 83,000 per annum with 11,000 deaths. 1 Most of the fatalities are due to the victim not reaching the hospital in time where definite treatment can be administered. In addition, community is also not well informed about the occupational risks and simple measures which can prevent the bite. It continues to adopt harmful first-aid practices, such as tourniquets, cutting, and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…For severe cases, intravenous infusion of neostigmine at 12 µg/ kg/hour can be administered. [1][2][3] Respiratory distress was resolved, and oxygen therapy and nebulisations were discontinued. The patient recovered and was discharged from hospital 5 days from admission.…”
Section: Descriptionmentioning
confidence: 99%
See 4 more Smart Citations
“…For severe cases, intravenous infusion of neostigmine at 12 µg/ kg/hour can be administered. [1][2][3] Respiratory distress was resolved, and oxygen therapy and nebulisations were discontinued. The patient recovered and was discharged from hospital 5 days from admission.…”
Section: Descriptionmentioning
confidence: 99%
“…Phospholipase A2 may cause myotoxicity and rhabdomyolysis. [1][2][3] Hypersalivation from envenomation by coral snakes is uncommon. In 2006 Bucaretchi et al 3 reported 1 case of moderate hypersalivation out of 11 (9.09%) cases of envenomwith Micrurus species in Brazil.…”
Section: Descriptionmentioning
confidence: 99%
See 3 more Smart Citations